GENEZA WCZESNOPIASTOWSKIEGO DWORU - Joanna Zięba (In Gremium. Studies in History, Culture and Politics, 2013)
The genesis of early Piast’s courtThe genesis of the forms of organisation of Piastów’s court and state embraces more than one aspect. Tribal organization forms had an overwhelming influence on the shape of Piastów’s magistratic andadministrative organization. The effects of time spread covering the period from family-tribal organization to monarchy were eliminated due to the preserved continuity of the process of changes. Particular elements of the administrative structures of the early Piastów’s state evolved mainly on the ground of tribal structures organization. Another factor that substantially contributed to the creation of Piastów’s power structure was the external influence. As a result of maintaining contacts with neighbouring European courts, Polish rulers took advantage of standards functioning in these courts while making changes or modernization.To ensure effective functioning and administering of a state, a well developed and efficient castle organization was required. In the early Piastów’s Poland, especially during the reign of Mieszko I, there began the process of modernizing the old and building new castles. Although there were few strong castles, the Polish state failed to have one main power centre. However, Gniezno is considered to have been the the first capital of Poland. It was due to the fact that Gniezno represented values of symbolic character at that time. However, Gniezno earned the greatest significance at the religious level, as it was a leader in the sacral structure of Piastów’s Poland. Another centre of power deserving the name of a central castle was Poznań; due to its location. Thanks to convenient communication water routes, Poznań became an important commercial and economic centre. In the area of a state being created, a significant role, apart from Gniezno and Poznań, was played by Ostrów Lednicki, Giecz as well as Moraczewo.